The logarithmic ACD model: The microstructure of the German and Polish stock markets - Gurgul, Henryk; Syrek, Robert (Managerial Economics, 2016)
The main goal of this paper is to compare the microstructure of selected stocks listed on theFrankfurt and Warsaw Stock Exchanges. We focus on the properties of duration on both markets and on fitting the appropriate ACD models. Because of the quite different levels of capitalization of stocks on these markets, we observe essential discrepancies between these stocks. Whilefor most German companies on the DAX30, the Burr distribution fits better than generalized gamma distribution, the latter distribution is superior in the case of the largest Polish companies. Analyzing series by hazard function, we note the similarity of hazard functions for companies on both markets, which tend to have a U-shaped pattern.